STUDI PENGARUH WAKTU, SUHU DAN JUMLAH DEHIDRATOR PADA DEHIDRASI RISINOLEAT MINYAK JARAK DENGAN P2O5 - M. Sitorus; S. Ibrahim; H. Nurdin; D. Darwis (Universitas Andalas, 2010)
The aims of study are to optimize the reaction’s parameters i.e. time, temperature, and amount of dehydrator’s agent on the dehydration of ricinoleic of castor oil into dehydrated castor oil (DCO) by mean P2O5. DCO is the mixed of linoleic acid (LA) and conjugated linoleic acid (CLA). Dehydration were carried out using various of time, temperature, and amount of dehydrator. The reaction medium was maintained under vacuum, gentle bubbling with nitrogen, magnetically stirred and used Zn’s powder as antipolymerization’s agent. The changes composition of DCO were analyzed by GC, and identification by FTIR and GC-MS and compared to CLA’s standard. Best result were obtain for 4 h, at 200°C and 3% (w/w) P2O5. DCO compositions were : 1.02% of (9c/t – 12c/t) linoleic; 41.97% of (9c/t – 12t/c) linoleic ; 19.50% of (9c/t – 11t/c) CLA ; 19.79% of (9t – 11t) CLA; and 0.90% of residual’s of ricinoleic. The yields of dehydration was 98.98%, and the decreased 92.98% intensities of –OH wives number in FTIR spectra’s castor oil comparison with DCO to indicated transform of ricinoleic by dehydration. Both wave number of alkenes (C=C) at FTIR DCO spectra was indicated to formed of conjugated alkenes (CLA). The ratio of CLA : linoleic was 0.92 : 1 with achievement of 63.5% relatively to CLA standard with ratio of CLA : linoleic was 1.45 : 1. Keywords: Time, Temperature, Amount of dehydrator, Dehydration of ricinoleic